The holy Qur'an - Tahirulqadri, Muhammad, 1951- (Minhaj-ul-Quran Publications, 2009)
The Holy Qur'an, word of Allah (S.W.T) was revealed to the beloved Prophet Muhammad (peace be upon Him) 14 centuries ago and has been recognized as the greatest literary masterpiece in Arabic. It is a source of immense inspiration, guidance and wisdom for millions of Muslims all over the world and wider humanity. There have been many English translations of the Holy Qur’an in the past. As the Arabic language is one of the richest languages in the world, containing many meanings and hidden depths, with no comparison in the English language, it can be difficult to convey the fullest and inner meanings of the sacred text of the Qur’an, and it often remains difficult to understand in its English translations.